Prevalence of Protein C Deficiency in the Healthy Population - Tait, R C; Walker, Isobel D; Reitsma, P H; Islam, S I A M; McCall, Frances; Poort, S R; Conkie, J A; Bertina, R M (Thrombosis and Haemostasis, 1995)
Reported prevalence rates for protein C (PC) deficiency in the population at large have varied widely. The differences presumably reflect the existence of an apparently high number of clinically recessive forms of the deficiency. In an attempt to document more precisely the prevalence of PC deficiency in the healthy population we have measured PC activity in just under 10,000 blood donors in the West of Scotland. After repeat testing of donors with low results and then further observation and selection, 32 donors were identified who had individual mean PC activities below the age- and gender-specific study reference range. Assessment of available first degree relatives, and also PC gene analysis in 23 of these donors, allowed identification of at least 14 with an inheritable deficiency (8 by both family study and gene analysis, 3 by family study alone and 3 by gene analysis alone). Two recurring and seven unique point mutations, only one of which has been previously described, were identified. The observed prevalence of inherited PC deficiency was 1.45 per 1000 (95% Cl, 0.79/1000 to 2.43/1000). However after correcting for the possibility of missing some genuine inherited deficiencies we estimated the prevalence to be as high as 1 in 500. All cases of hereditary deficiency were asymptomatic with regard to thrombosis and none had a strong family history of thrombosis. These findings confirm the rather frequent occurrence of asymptomatic individuals with PC deficiency and support the hypothesis that additional defects in the anticoagulant pathways may be required to confer a high-thrombotic-risk phenotype.